Upaya Pendidikan Kewarganegaraan dan Pancasila di Perguruan Tinggi dengan Pendekatan Social and Emotional Learning (SEL) dalam Mewujudkan Generasi Digital Berkarakter - Purwanto, Muhammad (Innovative: Journal Of Social Science Research, 2025)
Civic Education and Pancasila (PKn) in higher education plays an important role in shaping the character of Indonesia's younger generation. However, with the rapid development of information and communication technology, PKn education faces new challenges in shaping the character of students, especially in the digital world. This study was conducted to explore the application of the Social and Emotional Learning (SEL) approach in PKn education, with the aim of fostering a digitally literate generation with strong character. The focus of this research is to analyze how SEL can enhance students' social and emotional skills and to examine its impact on character development in the digital age. This study employs a qualitative approach using a literature review method. Various relevant literature on the application of SEL in PKn education at universities was analyzed to identify existing patterns. The literature sources used include journal articles, books, and research reports discussing the application of SEL in character education and the challenges faced in its implementation at universities. The research findings indicate that the application of SEL in PKn education helps students manage their emotions, build healthy social relationships, and enhance their understanding of Pancasila values. SEL also improves students' ability to address digital challenges more wisely. The application of SEL in PKn education is effective in shaping students' emotional intelligence and preparing them to face challenges in the digital world.